PERBANDINGAN KADAR SUKROSA DALAM MADU RANDU DAN MADU KELENGKENG DARI PETERNAK LEBAH DAN MADU PERDAGANGAN DI KOTA SEMARANG - Sumantri Sumantri; Aqnes Budiarti; Indah Parameita (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2013)
ABSTRACT Key words: cottonwoods honey, longan honey, sucrose, KCKT   Honey is a natural liquid that generally has a sweet taste and produced by the bees. Along with the increase in consumption of honey, honey adulteration grew a way to get the benefits. Sucrose sugar often added because its price is relative cheap. The content of sucrose become a measurement of the authenticity of honey. The spurious honey harm consumers because of different composition so that its benefits are also different.The purpose of this research is to determine the sucrose content and the quantitation of sucrose in longan honey and honey cottonwoods from beekeepers and honey trade in the City of Semarang using HPLC.Honey samples were taken randomized with three sample of cottonwoods and three longan honey from beekeepers area in Ngaliyan, Gringsing dan Ambarawa and honey trade in the City of Semarang. The determination of sucrose using HPLC system (Waters ec 2695) equipped with C18 column (C18 5um Sunfire; 4.6 x150mm) and detector UV (UV/Visible Waters 2489) at wavelength 190 nm. Mobile phase consisted of a mixture of acetonitrile and aquabides (75:25, v/v) with a flow rate of 1.0 mL/min.Research results showed that the average content of sucrose in honey samples cottonwoods and longan honey from beekeepers respectively 4,03% dan 2,98%, while the average level for the sample of cottonwoods and longan honey trade in the City of Semarang respectively 2,11% and 2,59%. The average level of sucrose from twelve samples meet requirements but the there are two samples that does not comply requirement of honey based on SNI-2004. There was no significant difference between the levels of sucrose honey cottonwoods and honey longan from beekeepers and honey trade in the City of Semarang.